PENGARUH KINERJA KEUANGAN DAN CORPORATE GOVERNANCE TERHADAP RETURN SAHAM PERUSAHAAN - RIAN SUMARTA (Media Bisnis, 2014)
The aim of this study is to analyze the influence of financial performances and corporate governance on share return. The financial ratios are return on equity, price earnings ratio, earnings per share and price to book value. The sample of this research is collected from Indonesian Stock Exchange over the three year period of 2009-2011 which have a corporate governance perception index. The results show that corporate governance has influence on share return, while price earnings ratio, earnings per share, price to book value, and return on equity do not have influence on share return.